2013
DOI: 10.1063/1.4795861
|View full text |Cite|
|
Sign up to set email alerts
|

Role of graphene defects in corrosion of graphene-coated Cu(111) surface

Abstract: Protection of Cu(111) surface by chemical vapor deposition graphene coating is investigated. The X-ray photoemission spectroscopy results do not reveal any signs of corrosion on graphene-coated Cu(111), and suggest perfect protection of copper surface against interaction with atmospheric gases. However, the scanning tunneling spectroscopy results show that cracks in the graphene sheet open up windows for nanoscale corrosion. We have shown also that such local corrosions are not only limited to the discontinuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 36 publications
5
64
0
1
Order By: Relevance
“…However as with SAMS and other materials, the performance of 2D materials will be greatly challenged by the presence of defects, topography, and material heterogeneities that exist on the surfaces of metal interconnect structures. Studies by Wlasny 495 and Schiver 496 have already shown that while at the macro scale graphene can prevent corrosion of Cu, defects and imperfections in the graphene can allow corrosion at the nano-scale that would not be acceptable in state-of-the-art metal interconnects.…”
Section: 15mentioning
confidence: 99%
“…However as with SAMS and other materials, the performance of 2D materials will be greatly challenged by the presence of defects, topography, and material heterogeneities that exist on the surfaces of metal interconnect structures. Studies by Wlasny 495 and Schiver 496 have already shown that while at the macro scale graphene can prevent corrosion of Cu, defects and imperfections in the graphene can allow corrosion at the nano-scale that would not be acceptable in state-of-the-art metal interconnects.…”
Section: 15mentioning
confidence: 99%
“…The barriers between them are usually not continuous or might have high defect density. The breaking of hexagonal symmetry of 3 the lattice of graphene may serve as gateways for molecules and ions, thus lead to local corrosive changes in the chemical structure of copper [25]. Furthermore, different faces of copper crystals create different interfaces with graphene layers.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, both the hydrocarbon (e.g., CH 4 or C 3 H 8 ) and the H 2 gas are introduced into the reactor for a couple of minutes to grow the graphene layer. Finally, the copper substrate covered with graphene films is cooled down to room temperature in an Ar atmosphere [15][16][17][18].…”
Section: Synthesis Of Cvd-graphenementioning
confidence: 99%